Formation of parametric images using mixed‐effects models: a feasibility study. (22nd December 2015) - Huang, Husan‐Ming; Shih, Yi‐Yu; Lin, Chieh
Abstract : Mixed‐effects models have been widely used in the analysis of longitudinal data. By presenting the parameters as a combination of fixed effects and random effects, mixed‐effects models incorporating both within‐ and between‐subject variations are capable of improving parameter estimation. In this work, we demonstrate the feasibility of using a non‐linear mixed‐effects (NLME) approach for generating parametric images from medical imaging data of a single study. By assuming that all voxels in the image are independent, we used simulation and animal data to evaluate whether NLME can improve the voxel‐wise parameter estimation. For testing purposes, intravoxel incoherent motion (IVIM) diffusion parameters including perfusion fraction, pseudo‐diffusion coefficient and true diffusion coefficient were estimated using diffusion‐weighted MR images and NLME through fitting the IVIM model. The conventional method of non‐linear least squares (NLLS) was used as the standard approach for comparison of the resulted parametric images. In the simulated data, NLME provides more accurate and precise estimates of diffusion parameters compared with NLLS. Similarly, we found that NLME has the ability to improve the signal‐to‐noise ratio of parametric images obtained from rat brain data. These data have shown that it is feasible to apply NLME in parametric image generation, and the parametric image quality can be accordingly improved with the use of NLME. With the flexibility to be adapted to other models or modalities, NLME may become a useful tool to improve the parametric image quality in the future. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We propose to use the non‐linear mixed effect (NLME) models to generate the parametric images. Intravoxel incoherent motion (IVIM) diffusion parameters including the fractional volume of capillary blood (Fv), the true diffusion coefficient (D) and the pseudo‐diffusion coefficient (D*) were estimated using voxel‐by‐voxel fitting of real diffusion‐weighted MRI data to the IVIM model. Compared to the non‐linear least‐squares (NLLS) fitting and the NLLS fitting with image smoothing (NLLS‐SM), the proposed NLME approach improves the parametric image quality.